2015
DOI: 10.1016/j.displa.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 0.2Hz varying latency with 20–100ms varying amplitude on simulator sickness in a helmet mounted display

Abstract: a b s t r a c tThe relationship between the occurrence of simulator sickness (SS) and varying latency in a helmetmounted display (HMD) was explored in this study. Previous work has always considered latency to be a constant. The aim of this research was to determine if a latency that varied over time would impact the experience of SS for HMD users. An object location task was used while viewing real, live video scenes via HMD. A planned comparisons approach was utilized with four experimental conditions, 2 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Periodic variations in display lag can occur during HMD VR due to system clocks, asynchronous processes, buffer times, and sensor drift errors (Wu et al, 2016). Kinsella et al (2016) and St. Pierre et al (2015) both examined the effects of periodic variations in display lag on cybersickness.…”
Section: Effects Of Periodic Display Lag On Cybersicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodic variations in display lag can occur during HMD VR due to system clocks, asynchronous processes, buffer times, and sensor drift errors (Wu et al, 2016). Kinsella et al (2016) and St. Pierre et al (2015) both examined the effects of periodic variations in display lag on cybersickness.…”
Section: Effects Of Periodic Display Lag On Cybersicknessmentioning
confidence: 99%
“…As they moved their heads, the video images of their surroundings were delayed by a variable or constant amount of time before presentation on the HMD 9 . St. Pierre et al (2015) found that cybersickness was greater when a variable display lag with a frequency of 0.2 Hz and an amplitude of 100 ms was added to their baseline system lag of ∼70 ms.…”
Section: Effects Of Periodic Display Lag On Cybersicknessmentioning
confidence: 99%
“…If the image is provided directly to the user, the user may suffer because of the delays. Especially, bidirectional communication delay is time-varying in nature and can trigger simulator sickness [11]- [13]. Also, random loss of image data, which is frequent because of the size of stereoscopic images, increases variation in CM .…”
Section: Overview Of the Display Systemmentioning
confidence: 99%
“…CM and OP are the predominant delays; IMU is both relatively small and constant. To reduce the undesirable effects of CM and OP (such as sickness [11]- [13]), we develop a predictive compensation algorithm. The algorithm modifies the delivered images…”
Section: Overview Of the Display Systemmentioning
confidence: 99%
See 1 more Smart Citation